Two critical N-terminal epitopes of the nucleocapsid protein contribute to the cross-reactivity between porcine epidemic diarrhea virus and porcine transmissible gastroenteritis virus. (17th January 2019) - Xie, Wenting; Ao, Chaojie; Yang, Yilin; Liu, Yinan; Liang, Rui; Zeng, Zhe; Ye, Gang; Xiao, Shaobo; Fu, Zhen F.; Dong, Wanyu; Peng, Guiqing
Abstract : Both porcine epidemic diarrhoea virus (PEDV) and porcine transmissible gastroenteritis virus (TGEV), which cause high mortality in piglets and produce similar clinical symptoms and histopathological morphology, belong to the genus Alphacoronavirus . Serological diagnosis plays an important role in distinguishing pathogen species. Together with the spike (S) protein, the nucleocapsid (N) protein is one of the immunodominant regions among coronaviruses. In this study, two-way antigenic cross-reactivity between the N proteins of PEDV and TGEV was observed by indirect immunofluorescence assay (IFA) and Western blot analysis. Furthermore, the PEDV N protein harbouring truncations of amino acids (aa) 1 to 170 or aa 125 to 301 was demonstrated to cross-react with the anti-TGEV N polyclonal antibody (PAb), whereas the truncation-expressing aa 302 to 401 resulted in a specific reaction with the anti-PEDV N PAb but not with the anti-TGEV N PAb. Mutants of the PEDV N protein were generated based on sequence alignment and structural analysis; we then confirmed that the N-terminal residues 58-RWRMRRGERIE-68 and 78-LGTGPHAD-85 contributed to the cross-reactivity. All the results provide vital clues for the development of precise diagnostic assays for porcine coronaviruses.